Dietary Cocoa Powder Improves Hyperlipidemia and Reduces Atherosclerosis in apoE Deficient Mice through the Inhibition of Hepatic Endoplasmic Reticulum Stress - Hua Guan; Yan Lin; Liang Bai; Yingfeng An; Jianan Shang; Zhao Wang; Sihai Zhao; Jianglin Fan; Enqi Liu (Mediators of Inflammation)
Cocoa powder is rich in flavonoids, which have many beneficial effects on human health, including antioxidative and anti-inflammatory effects. The aim of our study was to investigate whether the intake of cocoa powder has any influence on hyperlipidemia and atherosclerosis and examine the underlying molecular mechanisms. We fed apoE knockout mice a Western diet supplemented with either 0.2% (low group) or 2% (high group) cocoa powder for 12 weeks. The groups fed dietary cocoa powder showed a significant reduction in both plasma cholesterol levels and aortic atherosclerosis compared to the control group. Analysis of mRNA profiling of aortic atherosclerotic lesions revealed that the expression of several genes related to apoptosis, lipid metabolism, and inflammation was significantly reduced, while the antiapoptotic gene Bcl2 was significantly increased in the cocoa powder group compared to the control. RT-PCR analysis along with Western blotting revealed that a diet containing cocoa powder inhibited the expression of hepatic endoplasmic reticulum stress. These data suggest that cocoa powder intake improves hyperlipidemia and atherosclerosis, and such beneficial effects are possibly mediated through the suppression of hepatic endoplasmic reticulum stress.